TINDAK TUTUR NEGOSIASI DALAM BERMAIN PERAN SISWA SMK DAN PEMANFAATANNYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH - Panjaitan, Rosdiana Merianti (Universitas Tanjungpura, 2019)
AbstrakLanguage is one of the means of communication, through human language can interact (communicate) share experiences, learn from each other, and enhance intellectual abilities. In communication. The form of research used by researchers is qualitative, why? Because this research deals with qualitative characteristics. So the reason researchers chose qualitative forms were as follows (1) data collected in the original or natural conditions (2) Based on observations and interviews, (3) the data obtained from this study were in the form of words, pictures, and not numbers, (4) scientific setting, avoiding realities as provisions that cannot be separated from the context, Based on the results of data analysis, the final conclusions can be drawn about the speech acts proposed by Searle with the speech acts of negotiation in the role of class X AK 1 of Immanuel II Vocational High School II are (1) representative speech acts in the role of class X AK 1 student of SMK K Immanuel II act to inform something, show, explain, state, and express opinions, (2) directive speech acts in the role of students of class X AK 1 SMK K Immanuel II act for Requestives, Questions (questions), Requirements (Prohibitives) ( prohibit)`